IMPLEMENTASI PROGRAM ALOKASI DANA DESA DI DESA SEJEGI KECAMATAN MEMPAWAH TIMUR KABUPATEN PONTIANAK - Irman Riswandy E.42009009 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
Thesis writing is intended to identify and describe the process of policy implementation programs in the allocation of village funds Sejegi Village District East Mempawah Pontianak regency. The title of this thesis was appointed based on the existing problems in the implementation process of the village fund allocation program, implementation of the program refers to Pontianak decree No. 6 of 2010 on the Implementation of Village Fund Allocation instructions.District Government, District Government, and the Government of the village is in the process of implementation of the Leading Sector Allocation Village Fund program, the results of the study indicate that the process of implementation of the village fund allocation program is not running properly due to lack of compliance with the implementor of the duties and functions stated in regulation Regents Pontianak No. 6 in 2010.Lack of supervision of the district and sub-district to make the process of implementation of the program would be less than optimal. While the village government is implementing the policy has not done a good socialization to the community, so that the resulting lack of what touches people. key words: public policy, Impplementasi Public Policy, Rural Fund Allocation